Lipid Profile Improving Effect of Tenggulun Leaf (Protium javanicum) Tea Powder in Rats Fed with High-Fat Diet - Yusasrini, Ni Luh Ari; Darmayanti, Luh Putu Trisna (Jurnal Gizi dan Pangan, 2022)
The objective of this research was to determine the effect of tenggulun leaf tea powder in improving lipid profile in rats fed with high fat diet. We developed a tenggulun leaf tea powder and did a biochemical analysis. The in vivo study was conducted using 18 male Wistar rats grouped into three different diets, Control-Standard Feed (CSF) group, Hypercholesterol-Standard Feed (HSF) group and Hypercholesterolemia-Tenggulun Feed (HTF) group. The treatment was given for 30 days in all groups. Biochemical analysis showed that tenggulun leaf tea powder contains various cholesterol lowering substance such as dietary fibre (42.73%), phenolic content (9.42 mg GAE/g), tannins (10.80 mg TAE/g), flavonoids content (1.81 mg QE/g), and it also showed antioxidant activity (IC50 value of 67.20 ppm). In vivo analysis after treatment showed that there was no significant difference in total cholesterol levels between the HSF and HTF groups. However, in the HTF group there was a decrease in total cholesterol levels from the initial level by 16.48%. In addition, the HTF group had significantly higher HDL and lower LDL level compared to the HSF. The administration of tenggulun leaf tea powder for 30 days showed a significant effect on Low-Density Lipoprotein (LDL) and High-Density Lipoprotein (HDL) cholesterol levels, but not on serum Triglyceride (TG) levels. Therefore, the tenggulun leaf tea powder showed a significant effect in improving lipid profile in rats fed with high fat diet.